Cuidado de mães aos filhos na vigência do HIV mediante o uso da escala de avaliação da capacidade para cuidar de crianças expostas ao HIV - Freitas, Julyana Gomes (2010)
The Assessment Scale of the Ability to take Care of Children Exposed to HIV (EACCC-HIV) estimates mothers’ care delivery to children born in conditions of HIV. The goal was to assess mothers’ ability to take care of children exposed to HIV through the EACCC-HIV and to verify the association between scale dimensions and maternal characteristics. This cross-sectional study was carried out in Fortaleza-CE in 2010. Participants were 62 HIV+ caregivers (mothers) with 64 children (two twins) exposed to HIV at birth and younger than one year. The mothers and children’s characteristics were evaluated; strategies to reduce vertical HIV transmission: Family Apgar and EACCC-HIV. The scale contains 52 items and five factors, used for certain ages between zero and 1 year: Factor 1: ability to administer AZT syrup (children up to 42 days of life); Factor 2: ability to prepare and administer powder milk (children up to 1 year); Factor 3: ability to prepare and administer complementary feeding (children > 4 months); Factor 4: ability to administer prophylaxis with sulfamethoxazole and trimethoprim (children > 42 days); Factor 5: ability to guarantee adherence to clinical monitoring and vaccination (all children). Answers are mediated by a factor or by the sum of all items, indicating the degree of care the mother develops. STATA 11.0 software was used for analysis, with significance set at 5%. Maternal age ranged between 18 and 42 years, 33.9% suffering from aids, 61.3% in lower socioeconomic classes. One of the children had aids (1.6%), 98.4% had starting AZT in the first hours of life, 3.1% was breastfed, 61.3% showed inadequate artificial milk consumption and 36.2% inadequate complementary feeding consumption. The Family Apgar indicated 34.4% severely functional. While factor 1 of the EACCC-HIV assessed 11 children, 72.7% of whom received adequate care, factor 2 assessed 64 children and indicated high ability for care delivery in 86.0% of the mothers. According to factor 3, care was concentrated between moderate (44.4%) and high (50%). Factor 4 estimated the care offered to 53 children, indicating high ability for care delivery in 76.5%, and factor 5 assessed the 62 mothers’ answers on the 64 children. In total, 95.3% showed high ability for adherence to clinical monitoring and vaccination. According to the global assessment, 29.7% of care was considered adequate (high ability for care delivery). The association between variables indicated significance between family Apgar and ability to administer powder milk (factor 2); parity and ability to administer prophylaxis with sulfamethoxazole and trimethropim; parity and education level and ability to guarantee adherence to clinical monitoring and vaccination: and staging and diagnosis time with global assessment of the scale. Through the EACCC-HIV, maternal care for the children could be assessed and interventions could be made to enhance child health, with a view to maintaining quality of life in cases of exposure to or contamination by HIV.